ON THE STUDY OF MICROFLORA OF SEVAN LAKE BASIN WATERS (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Physico-chemical properties of the Lake Sevan water and underground and ground waters from boreholes of the Dzknaget River ostium region as well as the content of microorganisms in these waters were studied. Selected water’s samples are the basis for isolation of extreme forms of microorganisms.